SINGLE SHORT IMPLANT IN THE POSTERIOR MAXILLARY SECTOR. DIGITAL FLOW AND CROWN FABRICATION USING SINGLE UNIT TRANSEPITHELIAL. - Anitua, Eduardo (2023)
Abstract. Short and extra-short implants are most frequently used in the dental clinic. When they are used as a unitary rehabilitation, the diagnostic protocol and subsequent prosthesis confection must be careful in order to obtain the best results and the success of the treatment. To this end, the use of a drilling protocol appropriate to the residual bone and the fabrication of prostheses that minimize mistakes (digital flow and unitary transepithelial) are key, as we show in this clinical case.